Estado nutricional, função pulmonar e força muscular respiratória de indivíduos em hemodiálise submetidos à cinesioterapia respiratória - SOARES, Viviane (2011)
Individuals on hemodialysis show a reduction of muscle tissue which contributes to deficits in their activities of daily living and the ability to perform exercises. Given these factors and the possibility of changes in respiratory system is imminent. This study aimed to determine the nutritional status, to compare before and after a program of respiratory exercises the hematologicals and biochemicals parameters, muscle strength, lung function, changes in trunk volume and physical aspects related-self to quality of life. Nutritional status was determined by 24-hour recall (three days, one day of weekend), biochemical and hematological parameters (hematocrit, hemoglobin, total lymphocytes, urea, creatinine, albumin) and anthropometric measurements, triceps skinfold (TSF) and arm muscle circumference (AMC). Respiratory muscle strength was estimated by MIP (maximal inspiratory pressure) and MEP (maximal expiratory pressure). Lung function was assessed by the spirometric variables, FVC (forced vital capacity), FEV1 (end-expiratory volume in one second) and PEF (peak expiratory flow). For the kinematic analysis, was used 30 markers fixed on the trunk of the individuals. This, was divided at four compartments U-C (upper chest), L-C (lower chest), U-A (upper abdomen) and L-A (lower abdomen). Nutritional data were described as mean and standard deviation. For statistical analysis were used t student test and Spearman correlation coefficient. The nutritional profile detected losses in protein-energy consumption of these individuals. Serum concentrations of calcium and iron were below forecast in some individuals while consumption salt remained within the expected range for this population (1-3 g / day). Anemia was present in most individuals. Creatinine concentration was lower than recommended in most individuals. Anthropometric measurements showed a great variability among investigators when it was considered the age.The program of respiratory exercise improved scores on all dimensions of KDQOL- SF, a significant improvement in MIP, FVC and FEV1 (forced expiratory volume in one second) showing the effects of this therapy in improving muscle strength and pulmonary function in this population. Kinematic analysis showed that the volumes and their variations after exercises respiratory reflected an improvement in use of respiratory muscles. With regard to abdominal muscles, the activation of your muscle fibers have been small.